FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Natalia, Delvina; Santioso, Linda (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This study was conducted to find out what factors can increase company value in manufacturing companies listed on the Indonesia Stock Exchange in the 2018-2020 period. The sample selection through purposive sampling technique and valid data as many as 73 companies. The method used in processing the data is multiple linear regression analysis which is accommodated by the Eviews (Econometric Views) Student Version Lite for Windows and Mac released 12 and Microsoft Excel 2010. The results of this study indicate that risk management and profitability have a significant influence on the value of company. The implication of this research is the need to increase the disclosure of risk management information and increase the company's profitability so that it can increase the value of the company, as well as provide a positive signal for investors.